Северно-причерноморский ареал микро- и макротопонимии позднего праславянского языкового состояния - Шапошников, Александр (Nazwy terenowe i miejscowe w przestrzeni fizycznej, 2016)
Approximately in the 1st quarter of the I millennium AD the uttermost south-east area of Common Slavonic place names appear on North Azov shores and Don basin, and it contains that endemic hydronymy till today, despite the constant desertions, migrations, and settlement of different ethnic groups there. This region attracted attention of numerous home historians and philologists in XIX–XX centuries. That made possible to survey the greater part of archaic place names. Etymology, semantic evolution, correlation to real objects are reported in this article, as well as probable creators are detected for such micro- and macro- place and river names: Balta(chokrak), Berda, K(oƒsa) Berdinskaia, Britay, Britan’, Bug(a), Bulzyiab, Vitava, Βουλνηπράχ, Vir’, Vyr’, Βερούτζη, Dnieper, Dniester, Dunay, Idolga, Izlegoscha, Wielikoi, Maloi Ilanczik, Ilovay, Ilovl’a, Kaver’a, Kalitva, Kalitvina, Kalk[a], Kal’, Kalchik, coneſtāxe / conoſtaxi, copa, Kopyl, Lutik, Lugan’, Medveditza, Medobory, Metcha, Ναπρεζη̃, Nemyia, Nepr’adva, (Ν)Εσσουπη̃, Netecha, Νεασήτ, Obitok, Oleshie, Olschowat(ka), Opuk, Οστροβουνιπράχ, Paroy, Poroy, Plota / Polta, Protoch, Psiol, Ptan’, Rogan’, Saltov(ka), Seversky, Svidov(ka), Svidovat( aya), Svinoryi(ka), Σέρετος, Στρούκουν, Sųpoy, Ta(r)ganrog, Taųza, Tiveretz, Tim, Toloty, Tor, Toretz, Tuzha, Τουργανήρχ, Ųza, Ųtecha, Khortitza, Τζαρβαγάνιν, Cheremosh, Chertoroy, Chir.